Odor emoticon: An olfactory application that conveys emotions. Issue 91 (July 2016) - Xiang, Wei; Chen, Shi; Sun, Lingyun; Cheng, Shiwei; Bove, V. Michael
Abstract: Olfaction is an associative and emotional sense. The brain processes odors together with internal states, and odor-related memories contain strong emotional contents. This study focuses on people's emotional interpretations of odors, and proposes an olfactory application that uses odors as emoticons to convey emotions. This application offers an olfactory route for emotion communication, which can enhance communication experiences. Nine odor emoticons were designed, and validated through experiments. The effects of odor emoticons were also examined. A prototype system—Olfacticon—that emits odor emoticons was developed and applied in two contexts: online text chatting and voicemail receiving. Results suggested that odor emoticons induced more chatting, were easy to use, and helped participants perceive and convey emotions. Highlights: This paper proposes odor emoticon that use odors to represent emotions. Two experiments were conducted to design odor emoticons. Odor emoticons were applied in communication to examine their effects. Odor emoticons induced more chatting and helped people convey and perceive emotions.